2019
DOI: 10.1177/1753466619878128
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue is highly prevalent in patients with COPD and correlates poorly with the degree of airflow limitation

Abstract: Background: The objective of this study was to compare fatigue levels between subjects with and without COPD, and to investigate the relationship between fatigue, demographics, clinical features and disease severity. Methods: A total of 1290 patients with COPD [age 65 ± 9 years, 61% male, forced expiratory volume in 1 s (FEV1) 56 ± 19% predicted] and 199 subjects without COPD (age 63 ± 9 years, 51% male, FEV1 112 ± 21% predicted) were assessed for fatigue (Checklist Individual Strength-Fatigue), demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 59 publications
5
81
0
4
Order By: Relevance
“…Severe fatigue has been observed frequently in patients with chronic obstructive pulmonary disease (COPD) (ranging between 41 to 75%) [49][50][51], asthma (62%) [52], or cancer survivors (range from 7% to 52%) [53]. The current findings of severe fatigue of 48% and 69% in patients with IPF or sarcoidosis, respectively, fit well.…”
Section: Severe Fatigue In Patients With Ipf or Sarcoidosissupporting
confidence: 62%
See 1 more Smart Citation
“…Severe fatigue has been observed frequently in patients with chronic obstructive pulmonary disease (COPD) (ranging between 41 to 75%) [49][50][51], asthma (62%) [52], or cancer survivors (range from 7% to 52%) [53]. The current findings of severe fatigue of 48% and 69% in patients with IPF or sarcoidosis, respectively, fit well.…”
Section: Severe Fatigue In Patients With Ipf or Sarcoidosissupporting
confidence: 62%
“…Overall, the sarcoidosis patients had a mildly impaired lung function, which did not correlate with fatigue. Previous findings in patients with sarcoidosis [56], COPD [50], or asthma [52] showed that the forced vital capacity was not different between patients with and without severe fatigue, suggesting that the degree of lung function impairment does not play a major role in the development and/or maintenance of severe fatigue. In contrast, FEV1% predicted and TLCO% predicted were moderately correlated with CIS-Fat in the IPF patients, and severely fatigued patients had a significant lower diffusion capacity (p < 0.05) vs. no/mild fatigue.…”
Section: Factors Associated With Fatigue In Patients With Ipf or Sarcmentioning
confidence: 87%
“…A recent study of 1,290 patients with COPD reported that three-quarters had fatigue, evaluated by using the Checklist Individual Strength-Fatigue instrument. 38 Although fatigue was significantly associated with lung Interpretation of this first row is as follows: "If Patient A had a Physical Component Summary score that was 0.5 standard deviations higher than Patient B, then Patient A's expected fatigue score would be 5.0 points higher than Patient B." Each row reports the results of a separate regression model that evaluates the age-and sex-adjusted association of the variable named in the row at 6 months, with fatigue symptoms at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, people with chronic respiratory disease must continually adapt and learn to live with their respiratory and non-respiratory symptoms, and concomitant comorbidities, in their given social environments [15,16]. Preferably, this happens with optimal medical and therapeutic support from formal and informal caregivers.…”
Section: The Clinical Relevance Of Psychology and Behaviour Changementioning
confidence: 99%